A sexual rejection peptide: potential use for controlling mouse overpopulation. Issue 4 (3rd April 2019) - Osakada, Takuya; Itakura, Takumi; Kenmochi, Ryo; Touhara, Kazushige
ABSTRACT: Exocrine gland-secreting peptide 22 (ESP22) is a 10-kDa protein secreted in tears of juvenile mice. ESP22 inhibits sexual behaviors in adults, leading to a reduction in reproduction rate. We herein identified the 24 amino acid sequence within ESP22 that was essential for exhibiting sexual rejection activity. This synthesizable peptide can be useful for controlling mouse overpopulation.